Manual of infection prevention and control - Damani, Nizam (Oxford : Oxford University Press, 2012)
"It has been estimated that in developed countries up to 10% of hospitalized patients develop infections every year. Not only is there a substantial cost to healthcare systems, but some healthcare associated infections (HCIAs) can be fatal. Since the majority of HCIAs are preventable, reducing HCIAs is now considered to be an integral part of patient safety and quality of care provided by all healthcare institutions worldwide. Unlike other books on infection control, the main strength of this book is to provide clear, up-to-date and practical guidance in infection control in an easy to read format which can act as a quick source of reference on all aspects of HCIA for healthcare workers who are either directly or indirectly involved in prevention and control of HCIAs. Although the book's main audience is infection control practitioners such as doctors, nurses, public health physicians, it is also a valuable reference for environmental health officers, health educators, practice managers in GP surgeries, and health service managers"--
Machine generated contents note: -- Foreword, Professor Didier Pittet -- Preface -- Abbreviations -- Glossary of Infection Control Terms -- 1. Basic Concepts -- 2. Administrative Arrangement -- 3. Surveillance -- 4. Outbreak Management -- 5. Epidemiology & Biostatistics -- 6. Disinfection And Sterilisation -- 7. Isolation Precautions -- 8. Hand Hygiene -- 9. Personal Protective Equipment -- 10. Control Of Multi-Resistant Microorganisms -- 11. Special Pathogens -- 12. Intravascular Catheter-Related Infections -- 13. Catheter-Associated Urinary Tract Infections -- 14. Ventilator -Associated Pneumonias -- 15. Surgical Site Infections -- 16. Staff Health -- 17. Primary And Community Health Care Facilities -- 18. Support Services -- 19. Health Estates -- 20. Information Resource -- Index.
Originally published: Manual of infection control procedures. 2nd ed. Cambridge : Cambridge University Press, 2006.
Includes bibliographical references and index.
Keywords: Nosocomial infections -- Prevention; Hospital buildings -- Disinfection; MEDICAL / Infectious Diseases